Antifibrotic pyridine-containing monoterpene alkaloids from Caryopteris glutinosa. (November 2022) - Zhang, Xuejian; Cao, Yu; Pan, Dabo; Yao, Xiaojun; Wang, Fei; Zhang, Guolin; Luo, Yinggang
Abstract: Three undescribed dimeric pyridine-containing alkaloids, caryopterisines C – E, and four unreported cyclopenta[ c ]pyridine-derived alkaloids, caryopterisines F – I, were identified from Caryopteris glutinosa Rehder (Lamiaceae), together with two known monoterpene alkaloids. Caryopterisine C, featuring with an unprecedented 6/5/6/6/5 pentacyclic rings scaffold, may biosynthetically stem from a Diels-Alder reaction of two cyclopenta[ c ]pyridine-containing monomers and a following aromatization rearrangement reaction. Caryopterisines D and E, possessing an unprecedented 6/6/6/6/5 fused rings framework, may originate from a same Diels-Alder reaction of two monomers and subsequent aromatization arrangement, Baeyer-Villiger oxidation, and a set of tailoring reactions. Caryopterisine C showed strong inhibition on collagen accumulation in NIH3T3 cells (IC50 = 14.26 ± 1.46 μM). Caryopterisines G and I reduce collagen accumulation with IC50 values 88.91 ± 0.95 μM and 33.09 ± 1.38 μM, respectively. The Western blotting of the transforming growth factor- β -activated signaling pathways revealed that caryopterisine C inhibits collagen expression and accumulation via suppression of the phosphorylation of ERK1/2, P38, and SMAD2/3. The present works indicate caryopterisine C is a potential lead compound for the development of antifibrotic drugs. Graphical abstract: Image 1 Highlights: Pyridine-containing monoterpene alkaloids were identified from Caryopteris glutinosa. Caryopterisine C is a dimer featuring a unique 6/5/6/6/5 pentacyclic scaffold. Caryopterisines D and E are unique dimers possessing 6/6/6/6/5 fused rings. Caryopterisines C, G, and I reduce collagen accumulation in NIH3T3 cells. Caryopterisine C is a potential lead compound for antifibrotic development.